Mild therapeutic hypothermia after out-of-hospital cardiac arrest complicating ST-elevation myocardial infarction: Long-term results in clinical practice - Zimmermann, Stefan; Flachskampf, Frank A.; Schneider, Reinhard; Dechant, Katharina; Alff, Anna; Klinghammer, Lutz; Rittger, Harald; Achenbach, Stephan (Clinical Cardiology, 2013)
Background Recently, mild therapeutic hypothermia (MTH) has been integrated into the European resuscitation guidelines to improve outcomes after out-of-hospital cardiac arrest (OHCA). Data on long-term results are limited, especially in patients with acute ST-elevation myocardial infarction (STEMI). Hypothesis Invasive MTH influences long-term prognosis after OHCA due to STEMI. Methods We analyzed 48 patients who underwent emergency coronary angiography for STEMI after witnessed OHCA. In 24 consecutive patients, MTH was performed via intravascular cooling (CoolGard System, 34°C maintained for 24 hours) after initialization by rapid infusion of cold saline. Clinical, procedural, and mortality data were compared to 24 historical controls. Neurological recovery was assessed using the Cerebral Performance Category score (CPC) at 30-day and 1-year follow-up. Results Median time delay until arrival of emergency medical service was 6 minutes (MTH group) vs 6.5 minutes (controls) (P = 0.16). Initial rhythm was ventricular fibrillation in 75% vs 66.7% (P = 0.75). There were no differences regarding baseline characteristics, angiographic findings, and success of cardiac catheterization procedures. MTH was not associated with a higher frequency of bleeding complications or of pneumonia. Thirty-day mortality was 33.3% in both groups. One-year mortality was 37.5% (MTH group) vs 50% (controls) (P = 0.56). At 1 year, favorable neurological outcome (CPC ≤2) was significantly more frequent in the MTH group (58.3% vs 20.8%, P = 0.017). Multivariate analysis identified MTH as independent predictor of favorable neurological outcome (P < 0.02, odds ratio: 12.73). Conclusions MTH via intravascular cooling improves neurological long-term prognosis after OHCA due to STEMI and is safe in clinical practice. © 2013 Wiley Periodicals, Inc.
CRIS-Team Scopus Importer:2023-03-08